Intimacy Effects on Action Regulation: Retrieval of Observationally Acquired Stimulus–Response Bindings in Romantically Involved Interaction Partners Versus Strangers - Giesen, Carina; Löhl, Virginia; Rothermund, Klaus; Koranyi, Nicolas (Frontiers in Psychology, 2018)
Previous research has shown that stimulus–response (SR) binding and retrieval processes also occur when responses are only observed in another person (Giesen et al., 2014). Importantly, this effect depends on the two individuals interacting interdependently during the task (e.g., competition or cooperation). Interdependence, however, must not necessarily result from task-related demands, but can also reflect an intrinsic feature of a given relationship. The present study examines whether observing responses of one’s romantic partner also produces stimulus-based retrieval of observed responses even if the task itself does not involve interdependence. Participants performed a task pairwise, either with their romantic partner or with a stranger. In a sequential prime-probe design, both participants of a pair gave color responses themselves (actors) or merely observed these (observers) in alternating fashion. As expected, stimulus-based retrieval of observationally acquired SR-bindings occurred only in romantically involved pairs; participants interacting with a stranger showed no retrieval effects. We conclude that mental representations of self and other are more closely intertwined in romantic couples, which produces automatic retrieval of observationally acquired SR binding effects even independently of the task itself.